2015
DOI: 10.1007/s10803-015-2537-z
|View full text |Cite
|
Sign up to set email alerts
|

Network Approach to Autistic Traits: Group and Subgroup Analyses of ADOS Item Scores

Abstract: A network conceptualization might contribute to understanding the occurrence and interacting nature of behavioral traits in the autism realm. Networks were constructed based on correlations of item scores of the Autism Diagnostic Observation Schedule for Modules 1, 2 and 3 obtained for a group of 477 Dutch individuals with developmental disorders. After combining Modules, networks were obtained and compared for male versus female, high- versus low-functioning, seizure versus non-seizure, autism spectrum disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
3
17
0
2
Order By: Relevance
“…Most of them were compared with other disorders on one or two symptoms, such as depression [19] and obsessive-compulsive disorder [20], or evaluated with associated symptoms of autism [21]. What is consistent with our research results is that, in Anderson's studies about network analysis of autism, "social" and "communication" domains of Autism Diagnostic Observation Schedule (ADOS) ranked top two central items [21]; and the "anxiety" node in both ADOS and Revised Child Anxiety and Depression Scale (RCADS) items were highly peripheral [12,21], although previous study found a lack of correlation between items scores of CBCL and ADOS [22,23]. Here, "communication" was the most central node in the network, and "anxious/depressed problems" node in the CBCL items had relatively more peripheral centrality estimates.…”
Section: Central Symptoms In Asdsupporting
confidence: 85%
See 1 more Smart Citation
“…Most of them were compared with other disorders on one or two symptoms, such as depression [19] and obsessive-compulsive disorder [20], or evaluated with associated symptoms of autism [21]. What is consistent with our research results is that, in Anderson's studies about network analysis of autism, "social" and "communication" domains of Autism Diagnostic Observation Schedule (ADOS) ranked top two central items [21]; and the "anxiety" node in both ADOS and Revised Child Anxiety and Depression Scale (RCADS) items were highly peripheral [12,21], although previous study found a lack of correlation between items scores of CBCL and ADOS [22,23]. Here, "communication" was the most central node in the network, and "anxious/depressed problems" node in the CBCL items had relatively more peripheral centrality estimates.…”
Section: Central Symptoms In Asdsupporting
confidence: 85%
“…Accordingly, we designed the present study to explore the multidimensional relationships among these core symptoms and co-occurring symptoms of ASD. Network analysis [11,12] approach was used to assess the partial relationships of these symptoms in ASD. Rooted in physics and mathematics, network analysis is an integrative approach that can be applied in psychopathological research of mental disorders by establishing a network model to study the multidimensional relationships between symptoms and disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3) in both of which, samples and outcomes studied were heterogeneous. Anderson et al [84] studied autistic traits in a sample of children with Pervasive Developmental Disorder. They found that “usual eye contact” and “facial expression directed towards others” were the most important nodes.…”
Section: Resultsmentioning
confidence: 99%
“…Ils servent également de soutien à ces cadres théoriques en tant qu'outils complémentaires [36]. Par exemple, ils permettent de comparer les réseaux de personnes porteuses de troubles du spectre de l'autisme lorsque ce trouble est associé ou non à une déficience intellectuelle [37], de comparer un même ensemble de symptômes chez deux individus, d'étudier à…”
Section: Resultsunclassified
“…D'abord, en pratique, l'utilisation des réseaux de symptômes en clinique semble être aussi délicate à déployer (par exemple, du fait des contraintes liées à la modélisation informatique) que difficile à justifier (par exemple, concernant la plus-value par rapport aux classifications employées). Ensuite, en théorie, les débats sur le sujet dans la littérature spécialisée sont encore animés, allant de la défense pour leur replicabilité [39] à celle portant contre son réductionnisme [37], défenses qui pourraient conduire à la récupération de notions issues de la médecine personnalisée et d'autres disciplines, comme celles de driver adaptatif et d'addiction étiogénique [40]. Dans le fond, il est en effet bien légitime de se demander si les réseaux de symptômes pourront surmonter des problématiques inhérentes à leur propre constitution : comment vontils parvenir à privilégier un ensemble de mécanismes par rapport à un autre ?…”
Section: Les Research Domain Criteriaunclassified